Mobile marketing and its implementations - Latto, Joel (2014)
Latto, Joel Mobile marketing and its implementations Jyväskylä: University of Jyväskylä, 2014, 33 p. Information Systems Science, Bachelor’s Thesis Supervisor: Salo, Markus Mobile devices have become increasingly important marketing channel in recent years for all kinds of organizations. They allow marketers to bring forward relevant marketing information for the consumers based on location, purchase history, time and technology available. Although not brand new way of marketing, it is considered to be in its bloom right now, and it is expected to continue growing rapidly in near future. Some experts even say, that mobile marketing is just as vital to businesses as Internet marketing, and can soon even surpass – and partly fusion with - it as mobile phones are becoming consumers’ main tool of connecting to the Internet. This gives not just an excellent and fascinating base, but also a reason to study modern mobile marketing as a whole, to further gain understanding of what is the state of academic research on it, and what mobile technologies are implemented on this marketing channel. The thesis is based on a literature review conducted by using various academic article data-bases such as IEEE Explore and Microsoft Academic Search. The research was also enriched with recent literary and online resources. This allowed for more accurate description of the field, its technologies and its relations with traditional marketing channels.